Defining and Enabling ‘Justice’ for Victims/Survivors of Domestic Violence and Abuse: The Views of Practitioners Working within Muslim, Jewish and Catholic Faiths - Aghtaie, Nadia (Religion & gender, 2020)
The article is based on a qualitative field study of how justice (in its wider sense) is understood by practitioners and religious leaders from Judaism, Islam and Christianity, who work with victims of domestic violence and abuse. The article focuses on two key questions: a) how do practitioners from the three faith communities conceptualise justice in relation to domestic violence and abuse (DVA)? b) how far do these practitioners believe that victims of DVA have access to justice within their respective faith communities? The findings suggest that the concept of structural spiritual abuse should be given more attention by the DVA literature and also by those who are working with women of faith.